Reductive immobilization and long-term remobilization of radioactive pertechnetate using bio-macromolecules stabilized zero valent iron nanoparticles - Ji, Haodong; Yangmo Zhu; Duan, Jun; Liu, Wen; Zhao, Dongye (Chinese Chemical Letters, 2019)
Reductive immobilization of radioactive pertechnetate (99TcO4−) in simulated groundwater was studied by prepared carboxymethyl cellulose (CMC) and starch stabilized zero valent iron nanoparticles (nZVI), and long-term remobilization of reduced Tc was also evaluated under anoxic and oxic conditions. The stabilized nZVI can effectively reduce soluble 99Tc(VII) to insoluble 99Tc(IV), and they can be easily delivered into a contaminated groundwater zone and facilitate in situ remediation. In this study, CMC-stabilized nZVI showed higher reactivity than that using starch as the stabilizer. Batch experiments indicated that more than 99% of 99Tc(VII) (C0=12mg/mL) was reduced and removed from groundwater by CMC-stabilized nZVI with a CMC content of 0.2% (w/w) at a broad pH of 5–8. X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) analyses further confirmed that 99Tc(VII)O4− transformed into 99Tc(IV)O2 (s). The presence of bicarbonate exhibited insignificant effect on Tc immobilization, while humic acid (HA) inhibited reaction mainly due to retardation on electron transfer and formation of Tc(IV)-HA complexes. More interesting, the immobilized Tc(IV) remained insoluble even after 120 d under anoxic condition, while only ∼21% was remobilized when exposed to air. Therefore, bio-macromolecules stabilized nZVI nanoparticles could be a viable alternative for in situ remediation of radioactive contamination in groundwater.
Keywords: Groundwater; Radionuclide; Reductive immobilization; Stabilized nanoparticles; Technetium; Zero valent iron